St. Jack’s Experiment House for Juvenile Delinquents: Responding to Aslan’s Breath by Matthew Dickerson. - SALTER, G. CONNOR (Mythlore)
Matthew Dickerson raises an important point in his latest book "Aslan's Breath: Seeing the Holy Spirit in Narnia" that Lewis offers a theologically problematic example of combating evil when his heroes terrorize the bullies at Experiment House at the end of The Silver Chair. Exploring Dickerson's point, and particularly how Lewis pairs vengeance with saitre in this scene, challenges readers to see that Lewis' work for children is often more transgressive than it appears, not unlike the concerns raised about Roald Dahl's vengeful punishment scenes. Extending the popular Dahl vs. Lewis discussion shows how they both may be read as authors who intersect horror and humor, but for different ends.